The role of mitochondrial membrane potential and uncoupling protein 2 in hypoxic pulmonary vasoconstriction and pulmonary hypertension - Pak, Oleg; Justus Liebig University Giessen (My University, 2014)
The pulmonary vasculature constricts in response to acute alveolar hypoxia to redirect blood from poorly to better ventilated areas of the lung, which is an essential self-regulatory physiological response of the pulmonary vessels termed hypoxic pulmonary vasoconstriction (HPV). In contrast, different triggers of pulmonary hypertension (PH), including chronic hypoxia, lead to pathological reactions of the pulmonary vasculature, resulting in pulmonary vasculature remodeling that is characterized by excessive proliferation and attenuated apoptosis of vascular cells concomitant with reduction in the vascular lumen area. Despite intensive research in the last decades, the underlying mechanisms of HPV and vascular proliferation in PH have not yet been fully elucidated. It has been suggested that mitochondria play a key role in HPV, as well as in hypoxia and non-hypoxia dependent pathways that underlie pulmonary vascular remodeling. In both processes the mitochondrial membrane potential (MMP), which is an important characteristic of mitochondrial function and the main factor regulating the release of mitochondrial reactive oxygen species (ROS), could play a crucial role. It was hypothesized that knockout of the mitochondrial uncoupling protein 2 (UCP2) results in an increase of MMP and ROS emission that can regulate HPV and vascular remodeling in PH.Acute hypoxia induced an increase of MMP and ROS emission (O2 -, as well as H2O2) in pulmonary artery smooth muscle cells (PASMC) isolated from small precapillary arteries of rats and mice. MMP was also increased in precapillary PASMC isolated from experimental models of PH (chronic hypoxia-induced PH and monocrotaline [MCT]-induced PH) and from patients with idiopathic pulmonary arterial hypertension (IPAH) compared to respective controls. The increase of MMP in PH could have been the result of the utilization of increased glycolytically produced ATP, while concomitantly mitochondrial respiration was decreased in precapillary PASMC. Additionally, mitochondrial hyperpolarization could have also been mediated by UCP2 downregulation. UCP2 deficiency (UCP2-/-) caused an increase of MMP and ROS in small precapillary PASMC during normoxic baseline conditions and potentiated the increase of MMP and ROS in acute hypoxia. In parallel, UCP2 deficiency potentiated HPV and showed an increase of right ventricular systolic pressure (RVSP), right ventricle (RV) hypertrophy and vascular remodeling, thus mimicking PH in normoxic baseline conditions. The latter effect can at least partially be attributed to enhanced precapillary PASMC proliferation in UCP2 deficient mice that could be completely reversed by the application of the mitochondrial uncoupler, FCCP and partially by the treatment with ROS scavengers. These findings indicate a crucial role for mitochondrial hyperpolarization and increase of mitochondrial ROS emission in the development of PH. UCP2-/- mice exposed to 4 weeks of hypoxia did not display any differences in MMP compared to wild type (WT) controls. This finding can be explained by downregulation of UCP2 during chronic hypoxia as possible mechanisms to increase MMP in WT mice, which could not be activated in UCP2-/- mice during chronic hypoxia.The data of the current study thus suggest that an increase of MMP and ROS release could regulate HPV and vascular remodeling in PH. The mechanism for mitochondrial hyperpolarization in PH may be metabolic alterations and downregulation of UCP2 and was regulated by ROS. UCP2-/- deficiency lead to the development of the PH phenotype in mice via increase of MMP and partially via enhance of ROS emission in precapillary PASMC.

Die pulmonalvaskuläre Vasokonstriktion als Reaktion auf akute alveoläre Hypoxie dient der Umverteilung der pulmonalen Durchblutung von schlecht zu besser ventilierten Arealen der Lunge und ist ein essentieller selbstregulatorischer Prozess der Lungengefäße, der hypoxische pulmonale Vasokonstriktion (HPV) genannt wird. Im Gegensatz dazu führen verschiedene Auslöser, inklusive akuter Hypoxie, zu pulmonaler Hypertonie (PH), einer pathologischen Reaktion der Lungengefäße, die durch exzessive Proliferation und verminderte Apoptose von Gefäßzellen charakterisiert ist. Trotz intensiver Forschung in den letzten Jahrzehnten konnte der zugrundeliegende Mechanismus der HPV und der vaskulären Proliferation bei der PH noch nicht vollständig geklärt werden. Mitochondrien wurden als Schlüsselfaktor sowohl bei der Entstehung der HPV, als auch in Hypoxie-abhängigen und -unabhängigen Signalwegen des pulmonalvaskulären Gefäßumbauprozesses vorgeschlagen. Bei beiden Vorgängen könnte das mitochondriale Membranpotential (MMP), das eine wichtige Charakteristik der mitochondrialen Funktion und ein Hauptfaktor bei der Regulation der Freisetzung von mitochondrialen reactive Sauerstoffspesies (ROS) ist, eine wichtige Rolle spielen. Es wurde daher die Hypothese aufgestellt, dass die Ausschaltung des mitochondrialen Entkopplungsproteins uncoupling protein 2 (UCP2) zu einem Anstieg des MMP und der ROS Freisetzung führt, die die HPV und den vaskulären Gefäßumbau in der PH regulieren kann.Akute Hypoxie induzierte einen Anstieg des MMP und der ROS Freisetzung [Superoxid (O2 -), sowie Wasserstoffperoxid (H2O2)] in pulmonalen glatten Gefäßmuskelzellen (PASMC), die von kleinen präkapillären Arterien aus Ratten und Mäusen isoliert worden waren. Das MMP war auch in präkapillären PASMC isoliert aus experimentellen Modellen der PH [chronisch Hypoxie-induzierte PH und Monocrotalin (MCT)-induzierte PH] und von Patienten mit idiopathischer pulmonal-arterieller Hypertonie im Vergleich zu den entsprechenden Kontrollen erhöht. Der Anstieg des MMP in der PH könnte das Ergebnis einer Nutzung von vermehrt glykolytisch produziertem ATP gewesen sein, bei gleichzeitig verminderter mitochondrialer Respiration in präkapillären PASMC. Zusätzlich war die mitochondriale Hyperpolarisation möglicherweise auch durch eine UCP2 Herunterregulierung verursacht. UCP2 Gendefizienz bewirkte einen Anstieg des MMP und der ROS Konzentration in kleinen präkapillären PASMC während basaler, normoxischer Bedingungen und verstärkte den Anstieg des MMP und der mitochondrialen ROS Konzentration während akuter Hypoxie. Parallel dazu erhöhte die UCP2 Gendefizienz die HPV und UCP2-gendefiziente Tiere zeigten einen erhöhten rechtsventrikulären systolischen Druck, rechtsventrikuläre Hypertrophie und pulmonalvaskulären Gefäßumbau. Somit wurde durch die UCP2 Gendefizienz eine PH unter basalen, normoxischen Bedingungen imitiert. Dieses konnte wenigstens teilweise auf eine erhöhte präkapilläre PASMC Proliferation bei UCP2 defizienten Mäusen zurückgeführt werden, die komplett durch die Applikation des mitochondrialen Entkopplers, FCCP, und teilweise durch die Behandlung mit ROS Fängern rückgängig gemacht werden konnte. Dies spricht für eine entscheidene Rolle der mitochondrialen Hyperpolarisation und des Anstiegs der ROS Freisetzung bei der Entstehung der PH. Nach 4 Wochen Hypoxieexposition zeigten UCP2-/- Mäuse keinen Unterschied im MMP verglichen mit den Wildtyp (WT) Kontrollen. Dies kann durch die Herunterregulierung von UCP2 während chronischer Hypoxie als möglichem Mechanismus für die MMP Erhöhung in WT Mäusen erklärt werden, so daß dieser Mechanismus nicht bei den UCP2-/- Mäusen während chronischer Hypoxie aktiviert werden konnte.Die Daten dieser Studie legen daher nahe, dass ein Anstieg des MMP und der ROS Freisetzung die HPV und den vaskuläre Gefäßumbau bei der PH regulieren können. Der Mechanismus, der die mitochondriale Hyperpolarisation im Falle des vaskulären Gefäßumbaus verursacht, ist möglicherweise in metabolischen Veränderungen und einer Herunterregulierung von UCP2 begründet und wird durch ROS reguliert. Der Phänotyp der PH in UCP2-/- defizienten Mäusen wird durch ein erhöhtes MMP und teilweise durch eine erhöhte ROS Freisetzung in präkapillären PASMC unabhängig von metabolischen Veränderungen begünstigt.
Keywords: UCP2; ROS; mitochondria; pulmonary hypertension; PASMC; ddc:610